A metasurface‐based slit‐loaded wideband circularly polarized crossed dipole antenna. Issue 1 (7th September 2017) - Chen, Qiang; Zhang, Hou; Yang, Lu‐Chun; Zhong, Tao
Abstract: A metasurface‐based low‐profile crossed dipole antenna with wide circularly polarized bandwidth for 2.45 GHz ISM band wireless communications is proposed and fabricated in this article. Consisting of four slit‐loaded rectangular patches, the double‐sided printing crossed dipoles are fed by a pair of vacant‐quarter printed rings which circularly polarized (CP) radiation could be generated. With slits loaded, by properly combining the fundamental mode of the two inverted L‐shaped dipole, the slot mode and extra resonance generated by the AMC surface, a wideband circularly polarized operation can be obtained. After optimization, the final design with an overall size of 0.44λ0  × 0.44λ0  × 0.1448λ0 at 2.4 GHz had measured a 31.6% (2–2.75 GHz) impedance bandwidth and 3 dB axial ratio bandwidths of measured were 23.2% (2.1–2.65 GHz), respectively. In addition, the antenna performed a small gain variation (7.0–7.5 dBic) and a front‐to‐back ratio (FBR) of over 25 dB across the whole CP region.